PENGARUH PELAKSANAAN PROMOSI DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN MOBIL MITSUBISHI PAJERO SPORT PADA PT. DIPO INTERNASIONAL PAHALA OTOMOTIF PEKANBARU - Tesa Wenini; Endang Sutrisna (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This research was conducted at PT. Dipo Internasional Pahala Otomotif Pekanbaru which is located on Jl. Jend. Sudirman No.230, South Tangkerang, Bukit Raya, Pekanbaru, Riau. This study aims to determine the effect of Promotion Implementation and Brand Image on Purchase Decisions partially and simultaneously. This study uses a quantitative descriptive analysis method with the SPSS program. The population in this study were all consumers who purchased a Mitsubishi Pajero Sport car at PT. Dipo Internasional Pahala Otomotif Pekanbaru in 2020 was 179 and the sample in this study was 124 respondents. Determination of the sample in this study using the Slovin formula, namely the Non-Probability Sampling technique with the Accidental Sampling technique.Data analysis used validity test, reliability test, simple linear analysis, multiple linear analysis, determination analysis, and significance test with t-test (partial test) F test (simultaneous test). The results of this study indicate the results of the first t-test hypothesis, Promotion Implementation on Purchase Decisions, namely t count (13,107) > t table (1,6574) meaning that Promotion Implementation has a significant effect on Purchase Decisions. Second, the brand image on purchasing decisions is t count (10.319) > t table (1.6574) meaning that brand image has a significant effect on purchasing decisions. The results of the f test implementation of Promotion and Brand Image have a significant effect on Purchase Decisions, namely f count (104.976) > f table (3.07) meaning that the Implementation of Promotion and Brand Image simultaneously has a significant effect on Purchase Decisions for Mitsubishi Pajero Sports Cars at PT. Dipo Internasional Pahala Otomotif Pekanbaru. Keywords: Promotion Implementation, Brand Image, Purchase Decision